EFFECTS OF INTERNET ON EDUCATIONAL ACHIEVEMENTS, SOCIAL CAPITAL AND LIFE PATTERN OF YOUTH - Shahid Hussain,Muhammad Aslam Pervez (PJE, 2023)
This research study aimed at exploring the extent of internet usage among youth studying in various colleges and universities of twin cities of Rawalpindi/Islamabad and its ultimate effects on their educational achievements, life pattern and social capital. The study also tested the Time Displacement Hypothesis of Robert Putnam (1995), which postulates that heavy usage of media causes decline in the Social Capital and interpersonal communication of users with family, colleagues and friends and also decreases the social and physical activities of the users.